2007
DOI: 10.2967/jnumed.106.038182
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Quantitation of Glucose Metabolism in Mice Using Small-Animal PET and a Microfluidic Device

Abstract: The challenge of sampling blood from small animals has hampered the realization of quantitative small-animal PET. Difficulties associated with the conventional blood-sampling procedure need to be overcome to facilitate the full use of this technique in mice. Methods: We developed an automated blood-sampling device on an integrated microfluidic platform to withdraw small blood samples from mice. We demonstrate the feasibility of performing quantitative small-animal PET studies using 18 F-FDG and input functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 17 publications
4
88
0
Order By: Relevance
“…The FDG twotissue compartment model requires the plasma input function. The blood input function was converted to the plasma input function using the following equation [17]:…”
Section: Methodsmentioning
confidence: 99%
“…The FDG twotissue compartment model requires the plasma input function. The blood input function was converted to the plasma input function using the following equation [17]:…”
Section: Methodsmentioning
confidence: 99%
“…New microfluidic blood sampling devices were developed to minimize the amount of blood withdrawn (3). Another method minimizing blood losses is the use of an arteriovenous shunt, coupled with either a g coincidence counter (4) or a b probe (5).…”
mentioning
confidence: 99%
“…Slower glucose transport rates result in lower erythrocyte-to-plasma glucose distribution ratios in nonhuman primates; ratios ranged from 0 in pigs to 0.45 in calves (4). More recently, Wu et al confirmed that 18 F-FDG transport was also slow in mice; the 18 F-FDG concentration in plasma was initially significantly higher than in whole blood and did not reach steady state until approximately 20 min after injection (6). There was little animal-to-animal variability; estimation of plasma 18 F-FDG from whole blood values was possible using an empirically derived exponential function, but this would need validation for different experimental conditions such as diabetes (6).…”
mentioning
confidence: 63%